Tinjauan Sadd Adz-Dzari’ah Terhadap Ternak Liar Relevansinya Dengan Perdes No. 5 Tahun 2018 - Ma’arif, Badrul (Program Studi Hukum Ekonomi Syariah, 2023)
The background of this research is that the people of Burat village still release their animals, especially goats, sheep, and buffaloes, which are not in accordance with the provisions of the sad adz-dzari'ah law. This study aims to find out the practice of wild livestock in Burat Village, the level of community legal awareness and the factors that cause illegal livestock and to find out how the efforts of related parties to increase legal awareness of the importance of livestock in accordance with the sad adz-dzari'ah law. This research is a field research using a qualitative approach, in which the author observes the situation in the field and searches for existing data, then the author analyzes the level of legal awareness of the community by conducting interviews and direct observations. The data used are primary data taken through interviews with related parties releasing their animals in the village of Burat and secondary data taken from books, journals, articles, the internet and other library sources. The results showed that the level of knowledge and understanding of community law regarding wild livestock was still low, the factors causing residents to release their livestock were due to the level of community knowledge and understanding of the legal provisions of sad adz-dzari'ah and Perdes No.5 of 2108.